2012
DOI: 10.1021/es203177v
|View full text |Cite|
|
Sign up to set email alerts
|

Freshwater Availability and Water Fetching Distance Affect Child Health in Sub-Saharan Africa

Abstract: Currently, more than two-thirds of the population in Africa must leave their home to fetch water for drinking and domestic use. The time burden of water fetching has been suggested to influence the volume of water collected by households as well as time spent on income generating activities and child care. However, little is known about the potential health benefits of reducing water fetching distances. Data from almost 200, 000 Demographic and Health Surveys carried out in 26 countries were used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(152 citation statements)
references
References 37 publications
5
138
1
Order By: Relevance
“…A recent multi-country study found differences in water quality by water source type (Evans et al, 2013), but included studies reported little data on water quality by source type. Few studies analyzed distance to source in this review, which has been associated with child diarrhea, height, weight, and weight-for-age outcomes (Pickering and Davis, 2012). Meta-analyses have found that shorter distance to water source is associated with lower risk of diarrheal disease (Wang and Hunter, 2010) but not trachoma ; however, the trachoma meta-analysis contained many low-quality studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multi-country study found differences in water quality by water source type (Evans et al, 2013), but included studies reported little data on water quality by source type. Few studies analyzed distance to source in this review, which has been associated with child diarrhea, height, weight, and weight-for-age outcomes (Pickering and Davis, 2012). Meta-analyses have found that shorter distance to water source is associated with lower risk of diarrheal disease (Wang and Hunter, 2010) but not trachoma ; however, the trachoma meta-analysis contained many low-quality studies.…”
Section: Discussionmentioning
confidence: 99%
“…27 Analyses of DHS data have suggested increased distance to water source is associated with negative childhood health outcomes including diarrhea. 28 Utilizing measures of both distance and time for a round-trip would provide the most complete assessment of water fetching burden.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is demonstrated that, when the plot is closer to the home (less than 500 m), generally women spend less time cultivating it and are more motivated. Some authors [68,69] showed also a strong connection between the distance of the water source from the household (and the related time dedicated to women and children to collect water) and its positive effects in terms of productivity, nutrition, health and general empowerment, especially if the water source (especially clean water) is located less than 1 km from the village.…”
Section: The Water Gender Indicatorsmentioning
confidence: 99%